Asuhan Keperawatan Tn.”A” Dengan Gangguan Sistem Perkemihan: Post Operasi Prostatektomy - Sarma Eko Natalia Sinaga; Dian Harumawati Putri (Akademi Kebidanan La Tansa Mashiro, 2014)
The purpose of writing this Case Study is to be able to implement nursing care directly to Mr.